Prevalence of common mental disorders and associated factors among pregnant women attending antenatal care at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2023 - Temesgen, Kiber; Getnet, Berhanie; Asrat, Biksegn; Amare, Agegnehu (Frontiers in Psychiatry, 2025)
BackgroundCommon mental disorders (CMDs) such as depression and anxiety are prevalent during pregnancy. CMDs are public health concerns because of the implications for the health of both the mother and the fetus. This study aimed to determine the prevalence of CMDs and associated factors among pregnant women attending antenatal care at the University of Gondar Comprehensive Specialized Hospital (UoG CSH), Northwest Ethiopia.MethodsAn institution-based cross-sectional study was conducted from 26 September to 28 October 2023 among pregnant women attending antenatal care at the UoG CSH. Study participants were selected using a systematic random sampling technique. Data were collected using pre-designed tools like the Self-Reporting Questionnaire (SRQ-20) and the Oslo-3 Social Support Scale through face-to-face interviews. The collected data were entered into Epi data version 4.6.02 and analyzed using STATA version 14. Bivariable and multivariable logistic regression were used to identify factors associated with CMDs.ResultsOf the 407 pregnant women, 170 (41.8%) fulfilled the criteria for CMDs. In the multivariable analysis, financial instability (AOR = 1.66, 95% CI: 1.02, 2.69), poor social support (AOR = 2.60, 95% CI: 1.41, 4.81), emotional or physical abuse (AOR = 3.86, 95% CI: 1.79, 8.30), history of mental illness (AOR = 4.00, 95% CI: 1.24, 12.86), and unwanted pregnancy (AOR = 3.02, 95% CI: 1.02, 8.94) were significantly associated with CMDs.Conclusion and recommendationThis study indicated that the prevalence of CMDs was high among pregnant women attending antenatal care at the UoG CSH. Those who had financial instability, poor social support, emotional or physical abuse, history of mental illness, and unwanted pregnancy were prone to CMDs. Therefore, early screening and monitoring of CMDs among pregnant women are important to reduce possible negative impacts on the health of women.